Patient‐reported outcomes in patients with non‐alcoholic fatty liver disease: A narrative review of Chronic Liver Disease Questionnaire‐non‐alcoholic fatty liver disease/non‐alcoholic steatohepatitis. Issue 3 (16th July 2020) - Yamamura, Sakura; Nakano, Dan; Hashida, Ryuki; Tsutsumi, Tsubasa; Kawaguchi, Takumi; Okada, Michiaki; Isoda, Hiroshi; Takahashi, Hirokazu; Matsuse, Hiroo; Eguchi, Yuichiro; Sumida, Yoshio; Nakajima, Atsushi; et al.
Abstract: Non‐alcoholic fatty liver disease (NAFLD) is the most common liver disease worldwide and one of the leading causes of hepatocellular carcinoma and liver transplantation. Moreover, patients with NAFLD frequently complain of non‐specific symptoms including fatigue, abdominal discomfort, as well as anxiety, and NAFLD is reported to affect patient‐reported outcomes (PROs). Thus, for clarifying the total burden of NAFLD, it is crucial to assess all associated outcomes, including not only clinical and economic outcomes but also PROs. PROs are thought to reflect what is happening in one's daily life and is an important way patients and health‐care professionals communicate. There are various instruments for the assessment of PROs. Recently, a NAFLD/non‐alcoholic steatohepatitis (NASH)‐specific instrument called "Chronic Liver Disease Questionnaire (CLDQ)‐NAFLD/NASH" has been developed. CLDQ‐NAFLD/NASH comprises six domains: (i) abdominal symptoms, (ii) activity/energy, (iii) emotional health, (iv) fatigue, (v) systemic symptoms, and (vi) worry. CLDQ‐NAFLD/NASH has demonstrated excellent internal consistency, face validity, content validity, and test–retest reliability. It has been sufficiently validated in two international phase 3 clinical trials. In this review, we summarize features of various instruments for assessing PROs by focusing on CLDQ‐NAFLD/NASH. We also examine the validity of CLDQ‐NAFLD/NASH in Japanese patients and alterations in CLDQ‐NAFLD/NASH score in Japanese patients with significant hepatic fibrosis. Moreover, we discuss the utility of CLDQ‐NAFLD/NASH in phase 3 clinical trials and in a real‐world clinical setting.